2021
DOI: 10.1111/jne.13073
|View full text |Cite
|
Sign up to set email alerts
|

The electrophysiologic properties of gonadotropin‐releasing hormone neurons

Abstract: In the half century since GnRH was sequenced, studies using native GnRH decapeptide and antagonist analogs have demonstrated that the pattern of GnRH release is vital for normal physiology. The hypogonadal (hpg) mouse, a natural GnRH knockout, established this hormone as the critical final output from the central nervous system with respect to regulating the reproductive system through its effects upon the anterior pituitary gonadotropins luteinizing hormone (LH) and follicle-stimulating hormone. Although ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 180 publications
0
9
0
Order By: Relevance
“…All dendrons displaying the GABA B -mediated suppression showed a prompt rebound in intracellular calcium levels when the GABA or baclofen puff was stopped. This very likely represents a rebound in excitability mediated by hyperpolarization-activated cation and calcium channels known to be expressed by GnRH neurons ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All dendrons displaying the GABA B -mediated suppression showed a prompt rebound in intracellular calcium levels when the GABA or baclofen puff was stopped. This very likely represents a rebound in excitability mediated by hyperpolarization-activated cation and calcium channels known to be expressed by GnRH neurons ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of γ-aminobutyric acid (GABA) in the regulation of GnRH secretion has been a focus of investigation for more than 4 decades. Studies have reported substantial effects both of GABA A and GABA B receptor modulation on GnRH and luteinizing hormone (LH) secretion in multiple species as well as on GnRH neuron activity in rodents ( 5–12 ). However, without knowledge of the existence of the GnRH neuron dendron, this large body of work has been interpreted almost exclusively in terms of GABAergic modulation of the GnRH neuron cell body.…”
mentioning
confidence: 99%
“…The patterns of neural activity induced by noradrenaline were heterogeneous, ranging from bursting to a sustained Ca 2+ elevation. Bursting is commonly seen in neuroendocrine neurons, including magnocellular neurons (Brown et al., 2013 ) and GnRH neurons (Constantin et al., 2021 ), and has recently been recorded in vivo in CRH neurons (Ichiyama et al., 2022 ). Bursting is thought to be important in driving efficient exocytosis of large dense core vesicles from nerve terminals (Dreifuss et al., 1971 ; Dyball et al., 1988 ; Harris et al., 1969 ; Jackson et al., 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potassium channels have been shown to be modified by estradiol in other neuron types. [109][110][111] Regarding excitatory synapse properties, mEPSC frequency, amplitude, and decay robustly differed across the estrous cycle. Specifically, mEPSC frequency increased during early proestrus and estrus phases compared to diestrus phase, and significantly decreased in late proestrus phase compared to all other phases.…”
Section: Excitatory Synaptic Inputmentioning
confidence: 99%
“…One working hypothesis is that IRK potassium channel and voltage gated sodium channel expression both change in response to estradiol exposure, but in opposite directions. Potassium channels have been shown to be modified by estradiol in other neuron types 109–111 …”
Section: The Estrous Cycle Influences Nucleus Accumbens Core Msn Elec...mentioning
confidence: 99%